2015
DOI: 10.1007/s11832-015-0631-6
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic metal ion release occurs intraoperatively during correction and instrumented spinal fusion for scoliosis

Abstract: Study designProspective pilot study.ObjectivesThe aim of this study was to measure titanium, niobium and aluminium levels in various intraoperative and postoperative samples to determine patterns of metal ion release that occur within the first month following instrumented spinal fusion.Summary of background dataRaised serum metal ion levels are reported following instrumented spinal fusion in adolescent idiopathic scoliosis. The exact topological origin and chronology of metal ion release remains conjectural.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
1
24
1
Order By: Relevance
“…They concluded that their findings of contextually high metal ion concentrations in intraoperative and early postoperative samples provide further empirical support of a "putting-in" phenomenon of metal ion release following instrumented spinal fusion. This complements existing beliefs that metal ion release occurs during an intermediate "wearing-in" phase [28]. Lukina et al, in a retrospective study of implantation of titanium growth guiding sliding instrumentation for scoliosis in children, reported that the content of titanium and vanadium ions in the whole blood of 90% of patients with implanted LSZ-4D TM (CONMET, Moscow, Russia) devices was increased as compared with the control group (2.8 and 4 times, respectively) but did not exceed the values reported previously in the literature for fusion spinal instrumentation.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…They concluded that their findings of contextually high metal ion concentrations in intraoperative and early postoperative samples provide further empirical support of a "putting-in" phenomenon of metal ion release following instrumented spinal fusion. This complements existing beliefs that metal ion release occurs during an intermediate "wearing-in" phase [28]. Lukina et al, in a retrospective study of implantation of titanium growth guiding sliding instrumentation for scoliosis in children, reported that the content of titanium and vanadium ions in the whole blood of 90% of patients with implanted LSZ-4D TM (CONMET, Moscow, Russia) devices was increased as compared with the control group (2.8 and 4 times, respectively) but did not exceed the values reported previously in the literature for fusion spinal instrumentation.…”
Section: Discussionsupporting
confidence: 83%
“…Metal liberation from metallic implants has been reported in the body fluids of patients carrying total hip or knee replacements, intramedullary nails, and, more recently, in patients undergoing instrumental spinal arthrodesis [2][3][11][12][14][15][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical devices designed for such purposes can be made from a variety of biomaterials, but one of the most popular are Ti-based alloys (Geetha et al 2009 ). Many studies reported that titanium implants undergo biodegradation in the body (Matusiewicz 2014 ; Cundy et al 2015 ; Martín-Cameán et al 2015 ). Metal ions and biomaterial debris are released into peri-implant tissues as a result of corrosion and after this they can be transported by blood [Ti(IV) ions bound to transferrin] to other biocompartments (tissues) (Soto-Alvaredo et al 2014 ; Zierden and Valentine 2016 ).…”
Section: Introductionmentioning
confidence: 99%